2010
DOI: 10.1586/era.10.182
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies for treating relapsed/refractory urothelial carcinoma

Abstract: Advanced urothelial cancer is associated with a poor prognosis and there has been no substantial progress over the past three decades since the development of platinum-based multiagent chemotherapy. Clinical trials evaluating novel agents and combinations including chemotherapeutic drugs, as well as targeted inhibitors, are desperately needed. With a better understanding of the complex molecular alterations that drive urothelial tumorigenesis, new targets for novel therapeutics are being defined. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 119 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…128,146,245,247,[253][254][255][256][257][258][259][260][261][262][263][264][265][266] Among RTK, HER2 has been targeted in a multicenter phase II trial reported in 2007 by Hussain et al 267 Forty-four advanced BC patients with metastatic disease and evidence of tumor HER2 positivity by either immunohistochemical, FISH, or elevated serum extracellular HER2 domain levels, were treated with a combination of carboplatin, paclitaxel, and gemcitabine with the humanized monoclonal anti-HER2 antibody trastuzumab. 128,146,245,247,[253][254][255][256][257][258][259][260][261][262][263][264][265][266] Among RTK, HER2 has been targeted in a multicenter phase II trial reported in 2007 by Hussain et al 267 Forty-four advanced BC patients with metastatic disease and evidence of tumor HER2 positivity by either immunohistochemical, FISH, or elevated serum extracellular HER2 domain levels, were treated with a combination of carboplatin, paclitaxel, and gemcitabine with the humanized monoclonal anti-HER2 antibody trastuzumab.…”
Section: Targeted Therapy and Predictive Markers In Bladder Cancermentioning
confidence: 99%
“…128,146,245,247,[253][254][255][256][257][258][259][260][261][262][263][264][265][266] Among RTK, HER2 has been targeted in a multicenter phase II trial reported in 2007 by Hussain et al 267 Forty-four advanced BC patients with metastatic disease and evidence of tumor HER2 positivity by either immunohistochemical, FISH, or elevated serum extracellular HER2 domain levels, were treated with a combination of carboplatin, paclitaxel, and gemcitabine with the humanized monoclonal anti-HER2 antibody trastuzumab. 128,146,245,247,[253][254][255][256][257][258][259][260][261][262][263][264][265][266] Among RTK, HER2 has been targeted in a multicenter phase II trial reported in 2007 by Hussain et al 267 Forty-four advanced BC patients with metastatic disease and evidence of tumor HER2 positivity by either immunohistochemical, FISH, or elevated serum extracellular HER2 domain levels, were treated with a combination of carboplatin, paclitaxel, and gemcitabine with the humanized monoclonal anti-HER2 antibody trastuzumab.…”
Section: Targeted Therapy and Predictive Markers In Bladder Cancermentioning
confidence: 99%
“…Despite achievements in understanding the molecular pathogenesis of urothelial carcinoma of the bladder (UCB), no target-selective agents have been approved either as monotherapy or in combination with traditional chemotherapy in the treatment of metastatic or recurrent UCB [1]. Systemic chemotherapy with a platinum-based regimen remains the current standard of care for UCB patients [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Urothelial carcinoma of the bladder (UCB) is the most common type of bladder cancer that typically occurs in the transitional epithelium of urinary apparatus. Currently, there are no approved agents that can selectively suppress pathogenic molecular targets either as monotherapy or combination therapy in the treatment of metastatic or recurrent UCB (Iyer, Milowsky, & Bajorin, 2010). The current standard of care for the treatment of UCB is systemic chemotherapy using a platinum-based regimen (Gupta & Mahipal, 2013;Sternberg et al, 2013); however, approximately half of UCB patients are identified to have poor response (Cathomas, De Santis, & Galsky, 2015) or intolerable renal failure (Maeda et al, 2007).…”
Section: Pyrvinium and Urothelial Carcinoma Of The Bladdermentioning
confidence: 99%